Tsimshian narratives. - Barbeau, Marius, 1883-1969; Beynon, William, 1888-1958; Cove, John J.; MacDonald, George F. (Mercury series., 1987)
This collection of oral narratives from the Tsimshian Indians of the west coast of British Columbia around Prince Rupert, is illustrated with early photographs and maps, and reflects the close relationship of these people with their environment.